2014
DOI: 10.1007/s11302-014-9417-4
|View full text |Cite
|
Sign up to set email alerts
|

Striatal adenosine A2A receptor expression is controlled by S-adenosyl-L-methionine-mediated methylation

Abstract: Adenosine A 2A receptor (A 2A R) is a G proteincoupled receptor enriched in the striatum for which an increased expression has been demonstrated in certain neurological diseases. Interestingly, previous in vitro studies demonstrated that A 2A R expression levels are reduced after treatment with S-adenosyl-L-methionine (SAM), a methyl donor molecule involved in the methylation of important biological structures such as DNA, proteins, and lipids. However, the in vivo effects of SAM treatment on A 2A R expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…First, apart from facilitating H 2 S formation, SAM exerts a spectrum of biological effects, a number of which have been attributed to its methyl donor properties [ 37 ]. For example, a previous study reported that striatal adenosine A2A receptor expression is controlled by SAM-mediated methylation [ 14 ]. Therefore, we could not exclude the possibility that other mechanisms contribute to the regulation of P2X7R expression and NLRP3 inflammasome activation by SAM after ICH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, apart from facilitating H 2 S formation, SAM exerts a spectrum of biological effects, a number of which have been attributed to its methyl donor properties [ 37 ]. For example, a previous study reported that striatal adenosine A2A receptor expression is controlled by SAM-mediated methylation [ 14 ]. Therefore, we could not exclude the possibility that other mechanisms contribute to the regulation of P2X7R expression and NLRP3 inflammasome activation by SAM after ICH.…”
Section: Discussionmentioning
confidence: 99%
“…S -adenosyl- l -methionine, a CBS-specific agonist (SAM, Sigma-Aldrich, St. Louis, MO, USA), and sodium hydrosulfide, a classical exogenous H 2 S donor (NaHS, Aladdin, Shanghai, China), were diluted to concentrations of 100 mg/kg [ 14 , 15 ] and 5.6 mg/kg [ 7 ], respectively, in vehicle (saline) solution. The rats were treated intraperitoneally with SAM, NaHS or vehicle at 0.5 h after ICH.…”
Section: Methodsmentioning
confidence: 99%
“…Several agents have been implicated in the epigenetic regulation of ADORA2A, including transcription factors (CREB, NF-1, NFjB, PPARgamma, YY-1, and ZBP-89), proinflammatory cytokines (IL-1b and TNF-alpha), microRNA (miRNAs; miRNA-214, miRNA-34b, miRNA-15, and miRNA-16), and DNA methylation. [238][239][240][241][242][243][244][245][246][247][248][249][250][251] In polymorphonuclear leukocytes, the increase in A 2A R mRNA expression upon LPS stimulation correlates inversely with the expression levels of miRNA-214, miRNA-15, and miRNA-16. 247 Reduced miRNA-34b levels were related to increased A 2A R levels in the putamen of PD patients, although alterations in miRNA-214, miRNA-15, and miRNA-16 were not found.…”
Section: Regulation Of Adora2a Gene Expressionmentioning
confidence: 99%
“…Aminophylline, a competitive analogue to displace adenosine from its receptor, has been used for treatment and prevention of MTX‐related leukoencephalopathy . In addition, S‐adenosylmethionine, a cosubstrate involved in methyl group transfers, produced a significant reduction of Adora2a mRNA in a rat model and was suggested as a treatment option for depression and Alzheimer disease …”
Section: Discussionmentioning
confidence: 99%